2009
DOI: 10.1029/2009gl037353
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing lower thermosphere wind profiles using non‐specular meteor echoes

Abstract: [1] This article describes a new method of measuring wind velocity profiles between 93 km and 110 km altitude by tracking non-specular meteor echoes as neutral winds transport the plasma trails. This requires a large VHF radar with interferometric capability able to point nearly perpendicular to the geomagnetic field. A small data sample from the Jicamarca Radio Observatory allows the measurement of horizontal wind speeds and directions with a range resolution of a few hundred meters. These observations show s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 13 publications
4
55
0
Order By: Relevance
“…In the chemical release experiment by sounding rockets at different latitudes, longitudes, seasons, and local times, large horizontal winds and strong vertical shears have been measured (e.g., Wu and Widdel, 1992;Larsen, 2000Larsen, , 2002Larsen et al, 2005;Larsen and Fesen, 2009;Koizumi et al, 2009). Moreover, both the magnitudes and vertical structures of winds and shears measured by the sodium lidar and non-specular meteor radar are in line with those obtained by sounding rocket measurements (e.g., Larsen et al, 2003Larsen et al, , 2004Larsen and Fesen, 2009;Oppenheim et al, 2009Oppenheim et al, , 2014. Various wind measurement techniques indicated that large winds and wind shears occur frequently in the MLT region regardless of local times, seasons, latitudes, and longitudes (Larsen, 2002).…”
Section: Introductionsupporting
confidence: 63%
“…In the chemical release experiment by sounding rockets at different latitudes, longitudes, seasons, and local times, large horizontal winds and strong vertical shears have been measured (e.g., Wu and Widdel, 1992;Larsen, 2000Larsen, , 2002Larsen et al, 2005;Larsen and Fesen, 2009;Koizumi et al, 2009). Moreover, both the magnitudes and vertical structures of winds and shears measured by the sodium lidar and non-specular meteor radar are in line with those obtained by sounding rocket measurements (e.g., Larsen et al, 2003Larsen et al, , 2004Larsen and Fesen, 2009;Oppenheim et al, 2009Oppenheim et al, , 2014. Various wind measurement techniques indicated that large winds and wind shears occur frequently in the MLT region regardless of local times, seasons, latitudes, and longitudes (Larsen, 2002).…”
Section: Introductionsupporting
confidence: 63%
“…These trails have also been referred to as range-spread echoes [Malhotra et al, 2008;Mathews et al, 2008], spread meteor echoes [Reddi et al, 2002], and turbulent trail echoes, and they typically endure for less than a few seconds. They have been detected using both HPLA radars [Chapin and Kudeki, 1994;Oppenheim et al, 2009] and, less frequently, lowpower radars and are thought to result from Bragg scattering from field aligned irregularities (FAIs) in the trail [Heritage et al, 1962]; detection results from the growth of plasma instabilities. The time sequence associated with this process was summarized by Oppenheim et al [2000], who showed that an ambipolar E field (perpendicular to both the geomagnetic field and the trail) first develops, followed by a growth of plasma concentration waves on the edges of the trail that arise from the gradient drift/Farley Buneman instability and then, finally, plasma turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…However, a more detailed analysis of one of these fragmentation events and its corresponding trail revealed that these fragmentation influences do not account for all of the variation. Another suggestion could be that the neutral winds suddenly changed directions and caused the meteor trail to be "dragged" in the opposite direction of the original diffusion [Oppenheim et al, 2009], thereby causing an inflection point in the average variation of the meteor trail. However, we believe that the main factor for these large varying portions are due to detection of the meteor plasma in the initial stages of turbulence after the instabilities have grown large enough.…”
Section: Diffusion Perpendicular and Parallel To The Magnetic Fieldmentioning
confidence: 99%
“…Not only can we study the plasma from the meteors but we can also derive ambient ionosphere conditions. For example, Oppenheim et al [2009] developed a technique by which nonspecular meteor trails could be used to compute neutral wind measurements by comparing the phase differences between detection channels from the Jicamarca Radio Observatory [Oppenheim et al, 2009]. With these measurements, Oppenheim et al [2009] was able to discuss the influence of these neutral winds on the bulk fluid motion of the meteor trails in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation